(untitled) (Entrepreneurship Journal for Finance and Business, 2021)
This research aims to diagnose the mediating role played by reducing of cognitive conflict of human resources between managing the diversity of human resources and enhancing their strategic awareness towards their organization. As it is necessary to enhance the knowledge of human resources and reduce conflicts that may occur between them due to conflicting scientific and cultural orientations or backgrounds, In order to enhance their role in achieving their organization’s current and future strategies. Therefore, the research problem referred to the decline in knowledge and awareness of the importance of reducing the cognitive conflict and its role in managing the diversity of human resources and enhancing their strategic awareness towards their organization. so the researchers tried to embody the importance of his research in providing treatment for this problem and enhancing knowledge related to these variables within the investigated organization by achieving a set of goals. The descriptive analytical approach was adopted in carrying out the research in its various parts. The questionnaire was adopted in collecting data by distributing it to a sample of (97) individuals working at Al-Rafidain University College, and the statistical tools available in the (SPSS-V21) program were used to process the data, which produced a number of results that confirmed the validity of the research hypotheses and the strength of the correlation and influence relationships. Among the variables discussed, the researchers recommended the need to develop the methods and procedures adopted in managing the diversity of human resources by looking at the experiences of developed countries in this field, and employing its results in reducing their cognitive conflict, and then enhancing their strategic awareness towards their organization.